Genetic diversity of maize (Zea mays) hybrids based on protein analysis in different conditions - CHAUDHARY, ANJALI; YADAV, RASHMI (The Indian Journal of Agricultural Sciences, 2026)
Genetic variability of maize (Zea mays L.) hybrids grown in the fields is very important because genetic uniformityimplies risk of genetic vulnerability to stress factors and cause great loss in yield. Thus, knowledge of maize germplasm genetic diversity is important for planning breeding programmes, germplasm conservation per se. The systematic study to know the genetic architecture of the cultivars and their progenies has been improved by the incorporation of biochemical analysis especially of proteins as they portray the genetic base with more fidelity. Generally seed storage proteins have been used as markers in the analysis of genetic diversity within and among population as they are an impact of the genetic information existing on DNA. Under the present study the genetic diversity of 21 maize cultivars based on embryo protein markers through SDS & Native PAGE protein analysis was revealed differentiation from each other in both conditions. InSDS-PAGE more number of bands (22) was observed as compared to native PAGE (17). The dendogram using UPGMAwas constructed on basis of similarity matrix calculated by the presence/absence of protein fractions. Further clustering ofmaize accessions in dendogram were more in accordance with morphological traits like plant height, cob diameter etc. ascompared to native PAGE protein profiling. Thus, it can be concluded that SDS-PAGE either separately or together withagronomic traits is useful for genetic diversity studies in maize.